Public Perception of Heritage Buildings in the City-Centre of Invercargill, New Zealand - Aigwi, Itohan Esther; Filippova, Olga; Sullivan-Taylor, Bridgette (Elsevier BV, 2023)
With the global advancement in heritage conservation and sustainable management practices, understanding the public perception of built heritage is crucial. This paper examined the public perception of heritage buildings in the city centre of Invercargill, New Zealand, using an online survey to gather relevant information from over 600 participants. The results showed significant support (73.8%) for Invercargill City Council (ICC)'s district plan heritage list to be narrowed down as recommended by professional heritage consultants. There was also substantial support (72.6%) for heritage recognition of some recommended 26 buildings to be removed from ICC's district plan so that ICC can focus more on conserving fewer heritage buildings with significant values in the city centre. Many participants (66.1%) believed that a well-maintained heritage building and access to local government incentives should be the critical determinants for a heritage building to stay on ICC's heritage list. In addition, open-ended responses mainly emphasised the safety concerns of earthquake-prone heritage buildings and the expensive costs of seismic upgrades, suggesting the ‘demolition and rebuild’ of irrelevant heritage buildings as a feasible solution to redeveloping Invercargill's declining city centre. This study's findings revealed the significance of local knowledge of relevant built heritage parameters in Invercargill and its role in enhancing the usefulness of macro-level heritage projections and local built heritage conservation initiatives. These insights could serve as a starting point towards formulating a sustainable management plan for cities worldwide with ‘fast disappearing’ inner-city heritage buildings – a topic of interest for relevant built heritage conservation enthusiasts.
Keywords: 1205 Urban and Regional Planning; 1608 Sociology; 3304 Urban and regional planning; 4410 Sociology; 4702 Cultural studies